Características agronômicas e qualidade comercial de cultivares de milho pipoca em alta população - Fumagalli Leonello, Luiz Augusto [UNESP]; Cazetta, Disnei Amelio [UNESP]; Fornasieri Filho, Domingos [UNESP] (Univ Estadual Maringa, Pro-reitoria Pesquisa Pos-graduacao, 2009)
Agronomic characteristics and commercial quality of popcorn maize cultivars. In order to identify popcorn cultivars that constitute a viable alternative For popcorn producers, an experiment was conducted using a randomized blocks experimental design with Five genotypes (BRS Angela, Zelia, IAC 112, IAC 12 and IAC TC-01) and four repetitions, during the 2003/2004 crop. The experiment was carried out with 60 cm spacing between lilies and density of 75 thousand plants per hectare. During the experiment, agronomic and commercial characteristics were evaluated, under field and laboratory conditions. The variety BRS Angela featured increased yield, followed by simple hybrids IAC, with Zelia (triple hybrid) showing lower yield. The simple hybrid IAC 12 showed the lowest commercial quality of popcorn. Grain production was positively associated with the number of grains per car and with the weigh of 1,000 grains, and negatively with the level of N(total) in grain. The commercial quality was negatively influenced by the weigh of 1,000 grains.
Agronomic characteristics and commercial quality of popcorn maize cultivars.
Keywords: Zea mays L.; popping expansion; yield components